The association of antihypertensives with postural blood pressure and falls among seniors residing in the community: a case-control study - Zia, A.; Kamaruzzaman, S.B.; Myint, P.K.; Tan, M.P. (Blackwell Publishing, 2015)
Background: A drop in postural blood pressure (BP) may contribute to falls, while antihypertensives have been considered to induce postural drop or orthostatic hypotension (OH) and falls among older people. However, this relationship between antihypertensives, postural BP and the risk of falls has never been evaluated in a single study. Objective: To examine the association of postural BP changes and BP therapy with the risk of falls among community-dwelling older people in a case-control manner. Method: Cases (n = 202) included participants aged ≥ 65 years with two falls or one injurious fall while controls (n = 156) included participants ≥ 65 years with no falls in the preceding 12 months. Antihypertensives usage and medical history were recorded. Supine BP measurements were obtained at 10 min rest and at 1, 2 and 3 min after standing. Orthostatic hypotension was defined as a reduction in BP of 20/10 mmHg within 3 min of standing. Results: Individual antihypertensive classes were not associated with falls. Minimal standing systolic BP (SBP) was significantly lower among fallers [128 (± 27·3) vs. 135·7 (± 24·7) mmHg; P = 0·01], but fallers were not more likely to fulfil the diagnostic criteria for OH. Diuretics were associated with OH and α-blockers were associated with minimal standing SBP. Univariate analysis revealed that the use of ≥ 2 antihypertensives was associated with recurrent and injurious falls [OR,1.97;CI,1.2-3.1], which was no longer significant aftermultivariateadjustment for age and number of comorbidities [OR, 1.6; CI, 0.95-2.6]. Discussion: Minimal standing SBP or a lower SBP at 2 or 3minutes standing was associated with falls rather than OH using consensus definition. Association between ≥ 2 antihypertensives and falls was attenuated by increasing age and comorbidities. Our findings challenge previous assumptions that OH or the use of antihypertensives is associated with falls. Future studies should now seek to link these findings prospectively with falls in order to guide decision-making for BP lowering therapy among older patients.